Acrylamide Grouting: Successfully Controlling Groundwater From Canada To South America - Jom Gentry (Deep Foundations Institute)
Acrylamide chemical grout (C3H2NO) has been successfully used for over 50 years to control groundwater and stop infiltration. This paper will address three unique projects involving the control of groundwater with each study providing special circumstances and geological conditions: encapsulation of radioactive hazardous waste in the United States, a tailings dam for a large copper/gold mine in Argentina and 27 miles of leaking subway in Canada. The primary reasons for selecting acrylamide grout were based on the following characteristics: thinnest chemical grout on the market, a true solution grout which contains no suspended solids in the blended product, flexible gel set times, and a 362 year half-life in soil as determined by the U.S. Department of Energy.